(untitled) (Світ фінансів, 2017)
Клапків Ю. М. Спрямування інституціонального розвитку ринку страхування життя в Україні. Cформульовано концептуальні спрямування інституціонального розвитку ринку страхування життя. Означено особливості використання поняття “інституціоналізація” та “інститут” у страховій справі. Виокремлено етапи інституціоналізації та їх відображення на ринку страхування життя в Україні. Проаналізовано сучасний рівень розвитку ринку страхування життя. Досліджено характер інституціонального розви- тку ринку страхування життя, його фази. Клапкив Ю. М. Направления институционального развития рынка страхования жизни в Украине. Сформулированы концептуальные основы институционализации на рынке страхования жизни. Обозначены особенности использования понятий “институционализация” и “институт” в страховом деле. Выделены этапы институционализации и их отображение на рынке страхования жизни в Украине. Проанализирован современный уровень развития рынка страхования жизни. Исследован характер институционального развития рынка страхования жизни, его фазы. Klapkiv Yu. The institutionalization development of the life insurance market in Ukraine. Introduction. The evolution and society development, its institutions are continuous. The development of the life insurance market is also a complex. In Ukraine there is not the clearly organized and effective functional complex of life insurance. Especially problematic is the development of life insurance, without which no one systematic reform is impossible. Any development is realized through a conceptual basis, and the mandatory accumulation of financial resources for secured retirement. Purpose. The study is focused on the analysis of the current state of institutional development of the life insurance market in Ukraine. The aim of this article is a theoretical conceptualization of approaches to the concept of “institutionalization of the life insurance market,” and identify features inherent to the institutional development of the life insurance market. Results. The application features of institutionalization and the institution in the insurance business are analysed. The stages of institutionalization and their reflection on the life insurance market in Ukraine are determined. The current level of development of the life insurance market is analysed. The stance of institutional life insurance market is examined. The analysis of the institutionalization on political-legal, market and socio-cultural phases is realized. Absolute numbers relative reflect the market situation through a significant depreciation of the national currency, which combined with the economic crisis made a significant asymmetry of information. Conclusion. The process institutionalization of the life insurance in Ukraine is on the stage of objectification. The life insurance plays an important role in the lives of Ukrainians. The state refused from social security and functions, reduced the amount of pensions and increased the service. The market institutionalization of life insurance development conditioned to the significant decline in the socio-economic standard of living determines weak social and cultural development of the distribution of life insurance.